2012
DOI: 10.1159/000345554
|View full text |Cite
|
Sign up to set email alerts
|

Application of the PredictAD Software Tool to Predict Progression in Patients with Mild Cognitive Impairment

Abstract: Background: The PredictAD tool integrates heterogeneous data such as imaging, cerebrospinal fluid biomarkers and results from neuropsychological tests for compact visualization in an interactive user interface. This study investigated whether the software tool could assist physicians in the early diagnosis of Alzheimer’s disease. Methods: Baseline data from 140 patients with mild cognitive impairment were selected from the Alzheimer’s Disease Neuroimaging Study. Three clinical raters classified patients into 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The PredictAD tool developed by this group has been further evaluated. This software increased classification accuracy over clinicians provided with test results directly in paper form and improved inter-rater agreement and the rater’s confidence in their decision [417]. Liu et al [418] examined the efficacy of PredictAD software in predicting AD conversion within 3 years in comparison with currently recommended criteria for prodromal AD: episodic memory impairment, visual assessment of medial temporal atrophy, and abnormal CSF biomarkers.…”
Section: Methods Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…The PredictAD tool developed by this group has been further evaluated. This software increased classification accuracy over clinicians provided with test results directly in paper form and improved inter-rater agreement and the rater’s confidence in their decision [417]. Liu et al [418] examined the efficacy of PredictAD software in predicting AD conversion within 3 years in comparison with currently recommended criteria for prodromal AD: episodic memory impairment, visual assessment of medial temporal atrophy, and abnormal CSF biomarkers.…”
Section: Methods Papersmentioning
confidence: 99%
“…Simonsen et al [417] compared the accuracy of their PredictAD software with that of clinical raters asked to classify patients into a range of categories depending on their likelihood of developing the disease. The software increased classification accuracy over paper information alone from 63.2% to 70% and additionally improved interrater agreement and increased the raters’ confidence in their decision.…”
Section: Studies Of the Adni Cohortmentioning
confidence: 99%
“…In earlier studies, we have reported the DSI's ability to differentiate between AD and healthy aging [4] and the PredictAD tool's ability to provide decision support in predicting conversion from MCI to AD [8]. When comparing the three classification methods in this study, the DSI from the PredictAD tool performed significantly better than both the naïve Bayesian classifier and random forest at differentiating patients with AD from patients with other dementias.…”
Section: Discussionmentioning
confidence: 70%
“…Using their baseline data, clinicians predicted which subjects would progress to AD [8]. The prediction accuracy was significantly higher when using the PredictAD tool compared to using paper charts.…”
Section: Introductionmentioning
confidence: 99%
“…Disease State Index (DSI) and Disease State Fingerprint (DSF) [ 9 , 10 ] form a decision support system, first developed for the PredictAD diagnostic tool, to help clinicians in establishing the prognosis for patients with mild cognitive impairment (MCI) or to assist in the diagnosis between different dementia cases [ 11 , 12 , 13 ]. DSI functions as a classifier, measuring the similarity of the patient's data to that collected from populations with known diagnoses, i.e.…”
Section: Introductionmentioning
confidence: 99%